Organization of Eastern Caribbean States - Increasing Linkages of Tourism with the Agriculture, Manufacturing, and Service Sectors - World Bank (Washington, DC, 2012)
Tourism has become the leading economic sector of the Organization of Eastern Caribbean States (OECS) islands, thus expanding linkages with the local economy seems crucial going forward. Tourism has replaced agriculture as the main economic driver within all the islands comprising the OECS. In the early 1990s, agriculture contributed nearly 12 percent of Gross Domestic Product (GDP) overall; however by 2007 its share dropped to only 5 percent of GDP. Conversely, in the same year the tourism sector of these islands accounted for an estimated 45 percent of GDP, and around 60 percent of foreign exchange earnings, as a result of the more than 2.6 million tourists that visited these islands. This study analyzes the purchasing patterns and demand for agriculture, manufacturing and services by the tourism industry, both directly and indirectly, through a structured survey and in-depth interviews. A detailed survey covering 70 hotels, marinas, and other tourism operators analyzed the current purchasing pattern of agricultural and food products (13 categories from fruits to canned goods), services (12 categories, from legal support to flower arrangements), and manufactured goods (8 categories). From the supply side, 16 small and medium enterprises were surveyed on the obstacles they were facing for their development, and on their revenue and cost structures. Three different missions covered the 6 largest OECS islands, conducted over 80 interviews and included experts from the agricultural sector including Food Agriculture Organization (FAO) and Private Sector Development (PSD). Additionally, a value chain analysis evaluated the economics of key products. This combined approach provided an extensive source of data and information on linkages that was not available in the islands, as well as insights to improve them going forward. Overall, there seem to be interesting opportunities to increase linkages between tourism and other sectors of the OECS economies. Most hospitality operators, particularly hotels, demonstrate high willingness to increase the share of products and services purchased from local origin; and in addition, local suppliers of goods and services are willing to focus more their offer on the needs of the tourism industry. This study intended to provide some initial conclusions about specific economic activities and particular ways to increase such linkages in the agricultural and food, manufacturing, and services sectors.